Strategi Intervensi untuk Mengeliminasi Kasus Tuberkulosis - Putri, Anggreni Ade; Widati, Sri; Qomaruddin, Mochammad Bagus; Yunara, Yulia (Journal of Telenursing (JOTING), 2023)
This study aims to analyze tuberculosis intervention strategies in Southeast Asia. The method used is a systematic review. The Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) as a guide and The Joanna Briggs Institute (JBI) were used to conduct quality assessment. Data were born in the Scopus, Science Direct, and Pubmed databases on articles published in the last five years. In the final review, ten papers were included. The research results show that the intervention strategy is divided into three categories: community-based support through health cadres, nutritional status support, and investigation of household contacts and early detection. In conclusion, efforts to eliminate TB cases require a full-scale strategy with evidence-based interventions in identifying risk factors, contact investigation, and successful treatment. Keywords: Southeast Asia, TB Elimination, İntervention, Strategy, Tuberculosis